2016
DOI: 10.22302/ppbbi.jur.mp.v75i2.145
|View full text |Cite
|
Sign up to set email alerts
|

Biosorpsi logam Zn oleh biomassa Saccharomyces cerevisiae *) Biosorption of Zn metal by Saccharomyces cerevisiae biomass

Abstract: SummaryHeavy metal in waste water potentiallycauses environmental pollution. Generally,heavy metal pollutions come from metalplating, textile, latex-rubber goods, and otherindustries. The process of latex-rubber goodindustries uses heavy metal in the form ofZnO as accelerator for rubber vulcanizationprocess, so that Zn 2+ ion exists in wastewatereffluents in concentration as much as 300 ppm,whereas the maximum limit allowed is 2.5 ppm.The chemical way generally used to decreaseZn 2+ concentration in wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Pengaruh pH merupakan parameter yang penting pada penyerapan anion kromat (CrO4 2-). Pengaruh pH sangat diperlukan dikarenakan pada saat pengikatan antara gugus fungsi dengan anion kromat (CrO4 2-) melibatkan proses pertukaran ion H + [8].…”
Section: A Adsorpsi Anion Kromat Pada Silika Termodifikasi Dmaunclassified
“…Pengaruh pH merupakan parameter yang penting pada penyerapan anion kromat (CrO4 2-). Pengaruh pH sangat diperlukan dikarenakan pada saat pengikatan antara gugus fungsi dengan anion kromat (CrO4 2-) melibatkan proses pertukaran ion H + [8].…”
Section: A Adsorpsi Anion Kromat Pada Silika Termodifikasi Dmaunclassified
“…A. Penentuan pH pada Penyerapan Anion Kromat (CrO 4 ) 2-dengan Silika Termodifikasi DMA sebagai Adsorben Pengaruh pH sangat diperlukan dikarenakan pada saat pengikatan antara gugus fungsi dengan anion kromat (CrO 4 ) 2melibatkan proses pertukaran ion H + [7]. Penelitian kali ini dilakukan variasi pH dari pH 2, 4, 6, 8 dan 10.…”
Section: Hasil Dan Pembahasanunclassified
“…This technology has several advantages, including its high efficiency in binding trace metals, being regenerative, and the abundance of microorganisms that can be used as biosorbents. [22] Various biosorbents have been investigated to remove trace metals from solutions. Palar reported that fungi, bacteria, and yeast were used as biosorbents of trace metals such as Cr, Co, Ni, Zn, Ag, Au, Pb, Th, and U with absorption capacities varying from 0.4 to 450 mg g −1 [23] Pavasant et al used macroalgae to remove Cu 2+ , Cd 2+ , Pb 2+ , and Zn 2+ , and chitosan was used as a biosorbent for Pb 2+ ions.…”
Section: Introductionmentioning
confidence: 99%